Lightning - Steel, Danielle; McGillin, Howard (New York : BDD Audio Publishing, 1995)
"The story of a family thrust into uncertainty, forced to explore whether the bonds of love & marriage can withstand life's most unexpected bolts of lightning in the form of illness & career catastrophes"--Container.
Unabridged.
BDD Audio: BDDAP 560 (BDDAP 560A--BDDAP 560B).
Read by Howard McGillin.
Keywords: Domestic relations -- United States -- Fiction; Cancer -- Fiction; Audiobooks